2017
DOI: 10.1016/j.tsf.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

First-principles predictions of ruthenium-phosphorus and ruthenium-boron glassy structures and chemical vapor deposition of thin amorphous ruthenium-boron alloy films

Abstract: First-principles density-functional calculations are presented revealing that Ru(P) and Ru(B) alloys with moderate P or B content can result in a glassy structure exhibiting strong chemical short-to-medium range order. Amorphous phases are predicted to be energetically more favorable than the crystalline counterparts for the Ru(P) and Ru(B) alloys above ~20 at.% P and ~10 at.% B. The relative stability of amorphous and crystalline Ru(B) alloys is examined along with local atomic ordering in the amorphous alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Deposition is the most commonly applied process during the fabrication of thin films. According to the thin-film forming mechanism, deposition can be classified into chemical vapor deposition (CVD), such as low pressure CVD [38] and plasma enhanced CVD (PECVD) [39], and physical vapor deposition such as sputtering deposition [40][41][42], ion beam sputtering [43,44], thermal evaporation [45,46], pulsed laser deposition (PLD) [47,48], etc. This review mainly focuses on sputtering deposition and some other deposition processes are also proposed.…”
Section: Effects Of Different Deposition Parameters On the Surface Ro...mentioning
confidence: 99%
“…Deposition is the most commonly applied process during the fabrication of thin films. According to the thin-film forming mechanism, deposition can be classified into chemical vapor deposition (CVD), such as low pressure CVD [38] and plasma enhanced CVD (PECVD) [39], and physical vapor deposition such as sputtering deposition [40][41][42], ion beam sputtering [43,44], thermal evaporation [45,46], pulsed laser deposition (PLD) [47,48], etc. This review mainly focuses on sputtering deposition and some other deposition processes are also proposed.…”
Section: Effects Of Different Deposition Parameters On the Surface Ro...mentioning
confidence: 99%
“…Many studies [118][119][120][121][122][123][124] have demonstrated that some foreign elements, such as boron (B), phosphorus (P) and carbon (C) are able to induce the formation of amorphous Ru thin films and thereby significantly improve the ability of Ru thin films to prevent Cu interdiffusion. A 12 nm thin film of Ru (P) deposited on a low-κ dielectric layer effectively prevented the diffusion of Cu into Si wafer at 800 • C for 5 min [124].…”
Section: Platinum Group Metals (Pgm)-based Materialsmentioning
confidence: 99%
“…[15][16][17] Density-functional theory (DFT) calculations reveal that an amorphous layer structure is favorable, when the film shows a content of 20 at-% phosphorus. [18][19][20] Recently, a few studies for the formation of phosphorusdoped ruthenium layers by applying the PVD (= physical vapor deposition), CVD (= chemical vapor deposition) or ALD (= atomic layer deposition) process were reported. [16,17,21] In general, a dual source approach for Ru(P) thin film formation was implemented by using the triangular cluster Ru 3 (CO) 12 and different phosphines as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility for layer improvement is to dope ruthenium films with phosphorus, since such deposits provide a better inhibition of copper diffusion . Density‐functional theory (DFT) calculations reveal that an amorphous layer structure is favorable, when the film shows a content of 20 at‐% phosphorus …”
Section: Introductionmentioning
confidence: 99%